Answer :

LHS =

⇒ LHS =

⇒ LHS = = (sin^{2}A =1- cos^{2}A)

⇒ LHS =

⇒ LHS = =

⇒ LHS = = RHS

Hence Proved

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

<span lang="EN-USMaharashtra Board - Geometry Papers

<span lang="EN-USMaharashtra Board - Geometry Papers

Prove that:

</MHB - Mathematics Part-2

If <span lang="ENMHB - Mathematics Part-2

<span lang="EN-USMaharashtra Board - Geometry Papers

<span lang="EN-USMaharashtra Board - Geometry Papers

If tan θ = 2, finMHB - Mathematics Part-2

Prove the followiMHB - Mathematics Part-2

Choose the correcMHB - Mathematics Part-2

Prove that:

</MHB - Mathematics Part-2